Heat optimization in internal curing process of geopolymer mortar by using steel dust - Fan, Chin Yet (2015)
In conjunction with today competitive world, there was large amount of industrial wastes were produced with the rapid development of steel industry, which eventually lead to the disposal of these industrial waste in landfill and higher cost was required to reduce its impact on the environment. Among the industrial waste from steel industry, steel dust was one of the latest raw materials that has the ability to improve the geopolymer mortar performance on the mechanical properties due to its heat conductivity. It cannot be denied that the characteristic and mechanical properties of geopolymer mortar can be activated by elevated temperature of curing. But, the problem arose was the high temperature of curing can cause the shrinkage for geopolymer mortar and low durability. Meanwhile, low temperature curing cannot accelerate the strength improvement of geopolymer mortar. Owing to this, only few researches had been carried out to study the effect of steel dust as portion of fine aggregate replacement towards the heating optimization of internal curing process in geopolymer mortar. Thus, the experimental work presented here was aimed to study the effect of adding steel dust on the mechanical properties and water porosity of geopolymer mortar. In this study, steel dust was added to replace small proportion of fine aggregates in geopolymer mortar. Three different proportions of steel dust, which were 0%, 5% and 10% were added into the mortar with different curing temperatures of 50 oC and 60 oC. All cubes specimens were first oven cured for 1 day at 50 oC and 60 oC after the completion of casting in each mix. The specimens were then air cured for 1, 7 and 28 days at concrete laboratory before subjected to mechanical properties test. All cubes specimens were tested for its mechanical properties, which were compressive strength test and water porosity test. The results showed that addition of steel dust influenced the behavior of geopolymer mortar. Based on the laboratory test result, the geopolymer mortar with the addition of 10% steel dust and 50 oC curing temperature shows a conventional trend of high compressive strength with lower porosity, whereas for the addition of 10% steel dust and 60 oC curing temperature, it shows a non-conventional trend of high compressive strength, yet higher porosity as well. Conclusively, the results have validated the positive effect of steel dust addition into geopolymer mortar, particularly to the compressive strength enhancement. Geopolymer mortar with 10% steel dust addition as partial replacement for fine aggregates has appeared as the optimum proportion that contributed to the mechanical strength improvement of geopolymer mortar.